Efektivitas Latihan Rhytmic Stabilitation dan Combination Of Isotonic Terhadap Penurunan Nyeri pada Nyeri Punggung Bawah - Yuliana Ratmawati; Yoni Rustiana Kusumawati (Interest : Jurnal Ilmu Kesehatan, 2020)
Background: Low back pain is a complaint that is often encountered and very disturbing in carrying out daily activities. Myogenic pain is the most common complaint, around 49%.Physiotherapy modalities that can be given are Proprioceptive Neuromuscular Facilitation (rhythmic stabilization and combination of isotonic). Purpose this study to analyze effectivity rhythmic stabilitation exercise and combination of isotonic to decreased pain for myogenic pain. Methods: this research is two groups pre and post test design. Subjects: 30 subject diagnosed with myogenic pain in Dr Moewardi Hospital during the period between 2019 June –Augs. Results: The result of test toward pain effect between pre and post in group one after 3 weeks (6 times of therapy) is p = 0.009 with Wilcoxon test. The result of test toward pain between pre and post in group two is p = 0.001 and the test of pain between group one and group two shows p = 0.051. Conclusion: there is no difference in effect between the group one and group two toward the reduction of pain of patients with myogenic pain so that the results cannot be seen which is more effective.